(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Before effective advice about treatment alternatives can be delivered, a complete yet focused history, physical exam, and evaluation of the infertile female patient is required. The initial appointment is not only for gathering information to guide proper testing, but it is also for developing a relationship with the patient, which supports the demanding nature of infertility therapy. This is critical when the patient undergoes stressful and sometimes time-consuming treatment, disappointment due to unmet expectations, and frequently financially taxing choices. After a thorough review or after other, less expensive reproductive treatments have failed; the choice to proceed to in vitro fertilization (IVF) may be made. In all cases, the patient may not be psychologically, emotionally, or financially prepared for IVF, emphasizing the need of building a favorable rapport as part of the infertile woman’s or couple’s pre-IVF evaluation. The main purpose of this Research Paper is to create an overview on the medical specialty chronicles a clinical approach to infertile women and in vitro fertilization (IVF).